The Contribution of Cooperatives in the Development of Bheemdatta Municipality, Kanchanpur - Singh Thakuri, Bir Bahadur (Journal of Durgalaxmi, 2025)
This research investigates the involvement of cooperatives in facilitating socio-economic development in Bheemdatta Municipality, as well as building socio-economic engagement, changing mindsets, and enhancing livelihoods. Using a mixed-method design, information was gathered from 158 members, representing 265 cooperative households. The research findings indicate that cooperatives have resulted in both economic and social development. Access to credit soared from 26.4 to 86.8 percent after joining cooperatives. The number of households making less than NPR 10,000 fell from 32.1 percent to 13.2 percent, and households saving more than NPR 2,000 monthly increased from 13.2 to 35.8 percent. Households not investing in them fell from 39.6 to 7.5 percent. There was also social change, with school attendance regularly reaching 90.6%, year-round food security rising to 41.5, and a doubling of health care utilization (28.9% to 64.2%). The self-employment rate also increased from 20.7 to 54.7 percent. Though community opinion was acclaimable, 77.4 percent of respondents reported their attitude was positive, while 75.5 percent reported they trust their cooperatives. There were, however, some persistent obstacles, including low awareness (34%), financial capacity (30.2%), and moderate levels of active participation (with only 37.8% reporting they are very active). Overall, the research finds that cooperatives are an essential mechanism for financial inclusion and poverty reduction to enhance community well-being. Continued transparency, awareness, and inclusive governance will continue to strengthen the cooperatives development role in rural Nepal.